KNOW YOUR CUSTOMER PRINCIPLES (PMPJ) IN PREVENTING CRIMINAL ACT OF MONEY LAUNDERING - Susiani, Rini (International Journal of Psychosocial Rehabilitation, 2020)
Prevention and eradication of money laundering not only threatens the stability and integrity of the country's economy and financial system but also threatens the joints of life in society, nation, and state. This study uses a descriptive qualitative method, which aims to describe the additional audit procedures for PMPJ implementation. Data obtained through the study of journal literature and electronic media. The results of this study indicate an increase in the number of reports about alleged money laundering received by PPATK, indicating there is public awareness in supporting government policies in the prevention and eradication of money laundering through the determination of reporting parties and the establishment of Know Your Customer Principles for Accountants and Public Accountants in carrying out their profession and administrative sanctions from PPPK if the public accountant does not apply PMPJ.